Analysis Of Financial Knowledge, Financial Behavior, And Self-Control On Invesment Decision On Digital Platforms Among Generation Z - Desy Ramadani; Maya Syaula; Noni Ardian (Universitas Dehasen Bengkulu, 2026)
The rapid development of digital investment platforms has increased the participation of Generation Z in investment activities; however, the quality of investment decisions remains a concern. This study aims to analyze the effect of financial knowledge, financial behavior, and self-control on investment decisions on digital platforms among Generation Z. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 67 Generation Z students of Universitas Pembangunan Panca Budi Medan using purposive sampling. Data analysis techniques include validity testing, reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that partially, financial knowledge has no significant effect on investment decisions, while financial behavior and self-control have a positive and significant effect on investment decisions. Simultaneously, financial knowledge, financial behavior, and self-control significantly affect investment decisions. These findings suggest that behavioral and psychological factors play a more dominant role than financial knowledge in shaping investment decisions among Generation Z on digital investment platforms. Therefore, improving the quality of investment decisions requires not only financial literacy but also the strengthening of healthy financial behavior and self-control.